A rare case of ventriculoperitoneal shunt malfunction due to scrotal migration of the peritoneal catheter. (3rd September 2019) - Foster, Mitchell; Wilson, Graeme; Jenkinson, Michael D.; Buxton, Neil
Abstract: The authors describe an unusual cause of ventriculoperitoneal shunt malfunction presenting as acute hydrocephalus.